Public and decision-maker stated preferences for pharmaceutical subsidy decisions in Iran: an application of the discrete choice experiment - Gita Afsharmanesh; Farimah Rahimi; Leila Zarei; Farzad Peiravian; Gholamhossein Mehralian (Taylor & Francis Group, 2021)
Background The argument about funding criteria poses challenges for health decision-makers in all countries. This study aimed to investigate the public and decision-maker preferences for pharmaceutical subsidy decisions in Iran. Methods A discrete choice experiment (DCE) was used for eliciting the preferences of the public and decision-makers. Four attributes including health gain after treatment, the severity of the disease, prevalence of the disease, and monthly out of pocket and relevant levels were designed in the form of hypothetical scenarios. The analysis was done by using conditional logit analysis. Results The results show all of four attributes are important for pharmaceutical subsidy decisions. But a medicine that improves health gain after treatment is more likely to be a choice in subsidy decisions (by relative importance of 28% for public and 42% for decision-makers). Out of pocket, severity, and prevalence of disease subsequently influence the preferences of the public and decision-makers, respectively. The greatest difference is observed in changing the health gain after treatment and out of pocket levels, between public and decision-makers. Conclusion This research reveals that the public is willing and able to provide preferences to inform policymakers for pharmaceutical decision-making; it also sets grounds for further studies.